Bending behaviour of thin-walled perforated channel beams with modified cross-sectional shape – Part 1: experimental tests and FSM - Paczos, Piotr; Pawlak, Aleksandra M.; Jasion, Paweł; Plust, Michał (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
The subject of this study is thin-walled channel sections with a modified cross-sectional shape. The investigation involved six beams, three of which had perforations on the web, while the other three had a flat, solid web. The beams were subjected to four-point bending tests. Experimental tests were conducted using both electronic and optical methods, with a test setup specifically designed for this investigation. Additionally, numerical analyses were performed using the finite strip method. The primary objective of the research was to determine the impact of web perforations on the strength and stability of the bent beams. The perforation of the web also resulted in a reduction in the overall weight of the structure, thereby decreasing material consumption. Based on the research, the critical forces and maximum forces at which total loss of load-bearing capacity occurred were determined. Furthermore, the buckling modes of the beams were identified. The study revealed that the critical and maximum forces for beams with perforated webs were lower compared to beams with a flat, solid web. However, the significant reduction in weight for the perforated beams suggests that their use remains advantageous. The results of FEM and analytical analyses, essential for modelling and understanding complex behaviours in thin-walled structures, will be presented in the second part of this publication to maintain clarity and accessibility.